Estimation of Abbreviated Cyclosporine A Area under the Concentration-Time Curve in Allogenic Stem Cell Transplantation after Oral Administration. (26th October 2011) - ELjebari, Hanene; Ben Fradj, Nadia; Salouage, Issam; Gaies, Emna; Trabelsi, Sameh; Jebabli, Nadia; Lakhal, Mohamed; Ben Othman, Tarek; Kouz, Anis
Abstract : Measurements of Cyclosporine (CsA) systemic exposure permit its dose adjustment in allogenic stem cell transplantation recipients to prevent graft-versus-host disease. CsA LSSs were developed and validated from 60 ASCT patients via multiple linear regressions. All whole-blood samples were analyzed by fluorescence polarization immunoassay (FPIA-Axym). The 10 models that have used CsA concentrations at a single time point did not have a good fit with AUC0–12 (R 2 < 0.90 ). C 2 and C 4 were the time points that correlated best with AUC0–12 h, R 2 were respectively 0.848, and 0.897. The LSS equation with the best predictive performance (bias, precision and number of samples) utilized three sampling concentrations was AUC0–12 h = 0.607 + 1.569 × C 0.5 + 2.098 × C 2 + 3.603 × C 4 ( R 2 = 0.943 ) . Optimal LSSs equations which limited to those utilizing three timed concentrations taken within 4 hours post-dose developed from ASCT recipient's patients yielded a low bias <5% ranged from 1.27% to 2.68% and good precision <15% ranged from 9.60% and 11.02%. We propose an LSS model with equation AUC0–12 h = 0.82 + 2.766 × C 2 + 3.409 × C 4 for a practical reason. Bias and precision for this model are respectively 2.68% and 11.02%.